Le partage de l'Afrique et l'île d'Helgoland - Marcel, Gabriel (La Nature, 1890)
Keywords: Zanzibar

Anglo-German Treaty [Heligoland-Zanzibar Treaty] - Staatsarchiv; Blauhut, Adam (Sammlung der offiziellen Aktenstücke zur Geschichte der Gegenwart, 1891)
Keywords: Zanzibar

D'Aden a Zanzibar: un coin de l'Arabie heureuse le long des côtes - Roy, Alexandre Le (Alfred Mame et fils, 1899)
Keywords: Zanzibar

Über die Religiösen Anschauungen der ibadhitischen Muhammedaner in Oman und Ostafrika - Sachau, Eduard (Mittheilungen des Seminars für Orientalische Sprachen an der königlichen Friedrich Wilhelms-Universität zu Berlin, 1899)
Based on chapters 27, 29 and 40 of Sirḥān b. Saʿīd al-Izkawī’s Kashf al-Ghumma.
Keywords: Zanzibar

Das Gutachten eines muhammedanischen Juristen über die muhammedanischen Rechtsverhältnisse in Ost-Afrika - Sachau, Eduard (Mittheilungen des Seminars für Orientalische Sprachen an der königlichen Friedrich Wilhelms-Universität zu Berlin, 1898)
The Arabic text and translation of an answer by Yaḥyà b. Khalfān b. Abī Nabhān al-Kharūṣī, Qāḍī of Zanzibar, to questions asked him about the relationship between Shāfiʿī and Ibāḍī jurisprudence in East Africa, and about the most important Ibāḍī and Shāfiʿī Fiqh books. Imbert 1903b, 19-21: an abstract of Sachau’s article. Yaḥyà b. Khalfān al-Kharūṣī was Qāḍī of Zanzibar and he answered to questions posed by Sachau [via Mr. Rössler].
Keywords: Fiqh; Zanzibar

Über eine arabische Chronik aus Zanzibar - Sachau, Eduard (Mittheilungen des Seminars für Orientalische Sprachen an der königlichen Friedrich Wilhelms-Universität zu Berlin, 1898)
Sachau indicates the parts in Ibn Ruzayq’s al-Fatḥ al-Mubīn that are (almost) copied from Kashf al-Ghumma.
Keywords: Zanzibar

Muhammedanisches Erbrecht nach der Lehre der ibaditischen Araber von Zanzibar und Ostafrika - Sachau, Eduard (Sitzungsberichte der Königlich Preussischen Akademie der Wissenschaften zu Berlin, 1894)
Critical analysis and translation of the chapters on the law of succession (ch. 61-77) and testament (ch. 58) in Abū ‘l-Ḥasan ʿAlī b. Muḥ. b.ʿAlī al-Basyāwī’s Mukhtaṣar al-Basyawī (Zanzibar 1886). See Guidi, Ignazio 1906 for an Italian translation. Imbert 1903b: an abstract of Sachau’s translation (9-12) and a comparison with chapter 21 of Thamīnī’s K. al-Nīl, translated by Zeys 1895 (12-19).
Keywords: Fiqh; Zanzibar

Geschichte des Araberaufstandes in Ost-Afrika. Seine Entstehung, seine Niederwerfung und seine Folgen - Schmidt, Rochus (Verlag der königlichen Hofbuchdruckerei Trowitsch und Sohn, 1892)
Keywords: Zanzibar

Suaheli-schriftstücke in arabischer schrift: mit lateinischer schrift umschrieben übersetzt und erklärt - Büttner, Carl Gotthilf (W. Spemann, 1892)
Keywords: Zanzibar

Handbook of British East Africa, including Zanzibar, Uganda, and the territory of the Imperial British East Africa company. - Foster (War Office, 1893)
Keywords: Zanzibar